2010
DOI: 10.1111/j.1467-7717.2010.01119.x
|View full text |Cite
|
Sign up to set email alerts
|

Telocytes as supporting cells for myocardial tissue organization in developing and adult heart

Abstract: its morphogenesis. This study is designed to investigate the occurrence of telocytes in the developing heart and provide clues to better understand their role as supporting cells involved in the architectural organization of the myocardium during heart development. Our results showed that stromal cells with the immunophenotypical (vimentin, CD34) and ultrastructural features of telocytes were present in the mouse heart since early embryonic to adult life, as well as in primary cultures of neonatal mouse cardia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
82
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(86 citation statements)
references
References 14 publications
(25 reference statements)
4
82
0
Order By: Relevance
“…Cell communication plays an important role in the architectural organization and functional establishment of the myocardium [28,29]. Because the heart is a complex organ composed of many cell types, including cardiomyocytes and non-cardiomyocytes such as cardiac fibroblasts, smooth muscle cells, and endothelial cells, heterocellular communication between cardiomyocytes and non-cardiomyocytes is essential for cardiac development [18,19], heart physiology [30], and pathology [31]. It has been shown that myocardial cell maturation and function depend on the presence of endocardial endothelium cells [32], while cardiac fibroblasts mainly provide structural support during ventricular wall thickening from embryogenesis to adulthood [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell communication plays an important role in the architectural organization and functional establishment of the myocardium [28,29]. Because the heart is a complex organ composed of many cell types, including cardiomyocytes and non-cardiomyocytes such as cardiac fibroblasts, smooth muscle cells, and endothelial cells, heterocellular communication between cardiomyocytes and non-cardiomyocytes is essential for cardiac development [18,19], heart physiology [30], and pathology [31]. It has been shown that myocardial cell maturation and function depend on the presence of endocardial endothelium cells [32], while cardiac fibroblasts mainly provide structural support during ventricular wall thickening from embryogenesis to adulthood [33].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, telocytes participate in formation of the stem cell niche in the subepicardial region of the heart to guide cardiac stem cell development as well as closely embrace and nurse the growing cardiomyocytes as protector cells throughout the entire heart [16]. In addition, in vitro studies have shown that telocytes can intervene in the aggregation of cardiomyocyte clusters, which provides cues to guide the assembly of cardiomyocytes [18]. Indeed, the functions of telocytes have been mainly recognized based on their typical ultrastructural features, but their functions in the myocardium remain unclear.…”
mentioning
confidence: 99%
“…The clearest data have been obtained in the fetal and adult heart. In this organ, the TC seemed to be able, from one side, to build up cellular scaffolds to preserve the stem cells niches, from the other side, to organize 3-D pathways to guide the myocardiogenic stem cells organization and differentiation (66)(67)(68). In the gut, a similar role might be played in relation to the glandular stem cells (51,54) where a strict and privileged spatial interaction between these cells and the TC/PDGFRα + cells has been described.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac TCs have been identified in epicardium [10], myocardium [11], endocardium [12], subendocardium [13], stem cell niches [14], myocardial sleeves [15] and heart valves [16]. They form an interstitial network that plays a very important role in heart development, renewal and repair [17,18].…”
Section: Introductionmentioning
confidence: 99%